The Impact of Urbanization on Preserving the Miring Tradition among the Iban Community in Sungai Pasai, Sibu, Sarawak - Alexander, Chelum; Laura Pranti, Tutom; Asshadi, Mohamad Morni (Human Resource Management Academic Research Society (HRMARS), 2025)
Urbanization has reshaped the socio-cultural landscape of many indigenous communities worldwide, including the Iban of Sarawak, Malaysia. This paper examines the impact of urbanization on the preservation of Miring, a ritual deeply embedded in the Iban worldview as a symbolic offering to Petara (deities) and ancestral spirits. Using a descriptive qualitative approach, the study was conducted in Sungai Pasai, Sibu, where urban migration, modernization, and religious conversion have significantly altered cultural practices. Data were collected through participant observation of rituals, in-depth interviews with longhouse leaders, ritual experts (Lemambang), and community elders, alongside document analysis. The findings reveal that urbanization has led to a generational decline in the knowledge and practice of Miring. Younger generations, influenced by education, modern employment, and Christianity, often perceive the ritual as outdated. Additionally, the costs of ritual offerings and the dwindling number of ritual specialists have further weakened its practice. However, the study also uncovers resilience strategies, such as intergenerational teaching, embedding Miring elements within Gawai celebrations, and community-driven cultural clubs. These adaptations highlight the dynamic ways in which the Iban negotiate modernity while striving to preserve cultural identity. The paper concludes that while Miring faces existential threats in the context of urbanization, it continues to function as a cultural anchor for community cohesion and spiritual continuity. Efforts to safeguard the ritual should focus on community based education, documentation, and state-level cultural preservation policies.